2019
DOI: 10.1016/j.vetpar.2019.108973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the nutritional status of Creole goats on the density-dependent prolificacy of Haemonchus contortus

Abstract: The objective of this study was to measure the effect of the nutritional status of Creole goat kids on the host responses and the nematode population established after an experimental H. contortus infection. Fifty six kids were fed with 4 diets corresponding to 2 nutritional statuses: the low nutritional status (HAY, hay ad libitum and HB, Hay ad libitum + banana) and the high nutritional status (HS, hay ad libitum + soya meal and HSB, hay ad libitum + banana + soya meal). For each diet, 8 kids were experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Eosinophil counts were not influenced by any of the factors, although there have been reports that eosinophil counts decreased after the beginning of transportation in goats [5]. However, the results of the present experiment are in agreement with those of other authors [40] who reported that nutrition did not have any effect of eosinophil counts in creole goat kids.…”
Section: Differential Leukocyte Countssupporting
confidence: 91%
“…Eosinophil counts were not influenced by any of the factors, although there have been reports that eosinophil counts decreased after the beginning of transportation in goats [5]. However, the results of the present experiment are in agreement with those of other authors [40] who reported that nutrition did not have any effect of eosinophil counts in creole goat kids.…”
Section: Differential Leukocyte Countssupporting
confidence: 91%
“…This suggest that larval intake is a random process and is not directly proportional to time spent on infested areas. The non-linear relationship between FEC and adult parasite established within the abomasum, and consequently, larval ingestion could also explain our results (Cériac et al, 2019). Whatever, the biological interpretation resulting from our analysis should be interpreted with caution, due to the low number of monitored animals.…”
Section: Discussionmentioning
confidence: 80%
“…The feces were mixed homogeneously and FEC was estimated from 10 different samples (mean FEC = 576 eggs/g, std = 265 eggs/g). On week 2, feces were obtained from 16 experimentally infected animals with H. contortus (Cériac et al, 2019). FEC was assessed for each animal (mean FEC = 4431 eggs/g, std = 43.8 eggs/g), and feces were mixed together homogeneously.…”
Section: Stage 2: Grazingmentioning
confidence: 99%
“…An additional problem with supplementation is that we can connect that some animals may be reluctant to eat the supplements if they are not accustomed to them, or there might be existing competition between animals (6). The importance of dietary supplementation, especially protein supplementation, showed in numerous studies on resistance and resilience of sheep and goats to GI parasite infections, has been recently confirmed in a few studies (21,22). According to Hoste et al (23), GI parasitic infection is often equated to a nutritional disease because of the major negative impacts on total tract digestibility, diet intake, and the reorientation of nutrient use for the maintenance of tissue homeostasis.…”
Section: Discussionmentioning
confidence: 91%